Law, Media, and Democracy in the Digital Era: Freedom of Expression and ITE Regulation in Indonesia - Nilman Ghofur (Al-Mazaahib)
The digital era presents complexity in the discursive relationship between law, media, and democracy. This research analyzes the interconnection of these three aspects within the context of Indonesian identity. The study employs a literature review approach utilizing the framework of media discourse, focusing on three key areas: agenda setting, framing, and gatekeeping. Data sources include Article 28 of the 1945 Constitution and several articles within the ITE Law. The research reveals that in the practical application of law, media plays a significant role in conveying information and even shaping citizens' understanding of democracy. Several key findings surfaced from this investigation. Firstly, agenda-setting informs the public about the crucial significance of these matters within democracy. Secondly, by utilizing framing discourse, the media can influence public sentiment, whether by underscoring the importance of safeguarding privacy or portraying internet regulations as impeding freedom of expression. Lastly, this study unveiled how media organizations wield substantial control over the topics covered, thus determining what garners public attention. This control not only directs the agenda but also shapes public perceptions of laws related to democracy, underscoring the profound influence of media on societal comprehension.